JMJD1C promotes smooth muscle cell proliferation by activating glycolysis in pulmonary arterial hypertension - Chen Zhang; Yue Sun; Yingying Guo; Jingjing Xu; Haiyan Zhao (Cell Death Discovery, 2023)
Abstract Pulmonary arterial hypertension (PAH) is a chronic disorder characterized by hyperproliferation of pulmonary arterial smooth muscle cells (PASMCs). JMJD1C, a member of the Jumonji domain containing C (JMJC) histone demethylase family, contributes to cardiovascular dysfunction. However, the role of JMJD1C in PAH remains unknown. Mice were exposed to hypoxia to mimic several features associated with PAH clinically. We found that JMJD1C was highly expressed in the lungs of mice after hypoxia exposure. JMJD1C knockdown ameliorated hypoxia-induced right ventricular remodeling and thickening of the pulmonary arterial wall. PASMC hyperproliferation and resistance to apoptosis in mice exposed to hypoxia were suppressed by JMJD1C inhibition. We demonstrated that JMJD1C silencing reduced glycolytic enzymes (HK2, PGK1 and LDHA) and lactate overaccumulation in the lungs of mice exposed to hypoxia. In vitro, hypoxia-induced hyperproliferation and activated glycolytic processes in mouse PASMCs were impaired by JMJD1C knockdown. In addition, the activation of STAT3 signaling by hypoxia was suppressed by JMJD1C silencing both in vivo and in vitro. The overexpression of STAT3 reversed the inhibitory effect of JMJD1C depletion on proliferation and glycolysis in PASMCs under hypoxia. Thus, JMJD1C induces glycolytic processes by activating STAT3 signaling to promote PASMC proliferation and pulmonary vascular remodeling, suggesting the potential role of JMJD1C in regulating the metabolic program and vascular remodeling in PAH.